Formas de fazer ficção: de Final Fantasy VII ao livro eletrônico - Guimarães Neto, Ernane (2012)
This dissertation investigates ontological attributes of electronic games and books. This approach is founded on Philosophy, Communication and Ludology authors, contrasted and connected to each other. The principles in Nelson Goodman s nominalist philosophy ground the dialogue among different authors. A philosophy of language is constructed, aiming for the combination of concepts such as Heidegger s errancy and the thoughts on fiction since Plato and Aristotle. The tools obtained from this structure of relations are used for an interpretation of the Final Fantasy VII electronic game. Game researchers, such as Gonzalo Frasca and James Paul Gee, as well as Ludology epitomes such as Johan Huizinga and Roger Caillois, are summoned to support the understanding of this specific subject. From that game emerges a functional separation between independent narrative planes, related either to the fictional plot or playability. Following reflections on the ontology of electronic games, an exercise of translating Final Fantasy VII to e-book format is proposed. Marshall McLuhan helps thinking about the inherent potential in every new expressive medium; Walter Benjamin bridges traditional Western fiction and features of the reception experience, which are regained by digital media-laden interaction. Marie-Laure Ryan, among others who applied Literary Studies to understand games, complements the resulting e-book s conception. As a result, this research intends to accomplish a threefold role. It discusses language fundamentals and their ethical consequences for the work of communicators; analyzes a culturally relevant document in its mechanics and its fictional structure; presents an interactive book as an example of the electronic media potential in enriching the reading experience of fictional texts, even for non-game products